Effect of a Protocol to Reduce Radiographic Imaging in Pediatric Patients With Suspected Fractures. Issue 1 (12th January 2023) - Schlacter, Jamie A.; Roussos, Demetrios; Masrouha, Karim; Karamitopoulos, Mara; Carter, Cordelia; Price, Andrew; Castañeda, Pablo; Litrenta, Jody
Abstract : Background: Children with suspected fractures are typically evaluated with multiple x-rays. This approach can add time, discomfort, and radiation exposure without clinical benefit. The purpose of this study was to determine whether a focused radiographic protocol could reduce the number of x-rays performed without missing any fractures. Methods: Pediatric patients presenting at 2 sites within an academic medical center [urgent care (UC) and the emergency department(ED)] for a suspected fracture were identified. There were 495 patients (UC, 409; ED, 86) over a 3-month period. A retrospective chart review was performed to characterize the standard x-rays performed. Using this data, a simplified protocol was developed and distributed. Subsequently, 333 patients (UC, 259; ED, 74) were evaluated over the same period 1-year later. The main outcome measures included the final diagnosis, the total number of x–rays, the number of anatomic areas imaged, visit length, and the time for additional trips to radiology. Charts were reviewed to identify any missed injuries. Welch 2-sample t tests and Fisher exact tests were used for statistical analysis. Results: After implementing the radiographic protocol, there was a significant reduction in the number of x-ray views, 3.4 versus 5.1 ( P <0.001). There was a decrease in imaging of multiple anatomic areas with the largest reduction occurring in patients presenting with elbow injuries (9% vs. 44%, P <0.001). No difference was found in the rate of patients sent back to radiology (6% vs. 7%, P =0.67). However, among patients presenting with outside imaging, significantly fewer were sent to radiology for additional x-rays (29% vs. 50%, P <0.01). Conclusion: A simple radiographic protocol for evaluating pediatric patients with suspected fractures safely led to a decrease in the overall number of x-rays without missing any injuries. Level of Evidence: Level III, retrospective comparative study.